How to Be an Excellent Reviewer. (2nd September 2013) - Bednar, Carolyn
Abstract : This article will discuss what an editor expects for a quality review of a manuscript dealing with a research study. Reviewing a research paper requires more than academic knowledge and writing skills. It requires expert knowledge of the subject matter field plus expertise in research design and statistical methods.